Metabolomics: A new approach in functional food researches - Khatib, Alfi (2020)
A comprehensive analytical approach in research of functional food is currently becoming utmost important. This strategy leads to to the unbiased conclusion in the research. In this presentation, some applications of metabolomics in functional food study are discussed. Multi-platforms instrumental analysis is required since no single instrument is able to analyze whole range of compounds. The success of metabolomics depends on the right choice of statistical calculation to avoid the statistical error, of which multivariate data analysis is required. This presentation discussed the strategy on finding a best result using metabolomics by combining well standard of sample preparation, analytical method, multivariate data analysis, annotation of putative compounds, and in silico molecular docking.